TÓTH GUTTMAN EMESE - LAUDATIO - LUKÁCS, Olga (Studia Universitatis Babes-Bolyai Musica, 2023)
Dear Emese! We remember people in different ways. We only see you with a smile and serenity on your face, always on the move for music and its causes, or doing someone’s errands. When we ask you how you are, your answer is ‘quite fine’, and we immediately know what kind of music you are working on or what kind of courses or classes you are trying to start. Mihály Babits’s poem A második ének (The Second Song) fits you perfectly: “I'll tell you the secret of the song, my dear: He who listens to a song listens to himself. Every man has a song in his soul, and he hears his own soul in every song. And he who has a beautiful song in his soul hears the song of others as beautiful.” You were present at the start of our faculty’s music education programme in the first great teaching staff, and as a faculty member of the BBU Faculty of Reformed Teacher Education and Music from 2003, you have maintained the drive and loyalty we experienced about you in your first year. You encouraged your students to love music, to experience the delight and mystical world of music, and inspired by these encouragements your students have successfully performed in concerts, festivals, and competitions, both within and beyond the borders.